Associations of sodium intake with obesity, metabolic disorder, and albuminuria according to age. - Se Won Oh; Ho Seok Koo; Kum Hyun Han; Sang Youb Han; Ho Jun Chin (PLoS ONE, 2017)
Sodium intake is associated with obesity and metabolic disorder in the general population. However, sodium intake is significantly reduced according to the decrease of energy intake in older adults although the prevalence of obesity is higher than younger adults. We evaluate the association of sodium excretion (UNa) with blood pressure, obesity, metabolic disorders, and albuminuria according to age. An observational study using data from the Korean National Health and Nutrition Examination Survey IV-V (2008-2011) was performed (N = 18,146). The 24 hour UNa was estimated from a single fasting urine sample.Participants aged≥75 years showed the highest risk for hypertension (HTN) in the highest quartile of UNa (1.769, 95% CI, 1.174-2.665), and the risks for HTN increased with advancing age. Obesity was not associated with UNa in participants aged≥75 years, and hypertriglyceridemia and body fat were not related to UNa in participants aged≥65 years, although these values were significantly associated with UNa in participants aged<65 years. Impaired fasting glucose (IFG) and insulin resistance (IR) were associated with UNa only in participants aged 20-39 years. The highest quartile of UNa showed a 3.777 fold increased risk for albuminuria in those aged 20-39 years (95% CI, 1.130-12.630), and a 1.885 fold increased risk (95% CI, 1.156-3.075) among participants aged 40-64 years. In participants aged≥65 years, albuminuria was not associated with UNa. In contrast with HTN, UNa was not associated with albuminuria, obesity, hypertriglyceridemia, IFG, and IR in older adults despite a strong association in younger adults.